A novel surgical–prosthetic approach for soft tissue dehiscence coverage around single implant. Issue 9 (27th August 2012) - Zucchelli, Giovanni; Mazzotti, Claudio; Mounssif, Ilham; Mele, Monica; Stefanini, Martina; Montebugnoli, Lucio
Abstract: Objectives: The aim of the study was to evaluate soft‐tissue coverage and patient aesthetic satisfaction of a novel surgical–prosthetic approach to soft tissue dehiscence (STD) around single endosseous implant. Material and methods: Twenty patients with buccal soft tissues dehiscence around single implants in the aesthetic area were consecutively enrolled. Treatment consisted in: removal of the implant supported crown, reduction in the implant abutment, coronally advanced flap in combination with connective tissue graft (CTG) and final restoration. The unrestored contralateral tooth normally positioned without recession defect was used as a reference. The soft tissue coverage and patient satisfaction were evaluated 1 year after the final restoration. Results: One‐year mean STD coverage was 96.3%, and complete coverage was achieved in 75% of the treated sites. The increase (1.54 ± 0.21 mm) in buccal soft tissue thickness (STT) at 1 year was significantly correlated with CTG thickness at time of the surgery. The mean difference between graft thickness and STT increase was 0.09 ± 0.14 mm, corresponding to the 5.8% of the original graft thickness. The aesthetic analysis showed a significant improvement between the baseline (median, 3.8; 95% CI, 2–4) and the 1‐year (median, 8.0; 95% CI, 8–10) visual analogue scale (VAS) scores. Conclusion: The results from the present study demonstrated that the proposed bilaminar technique was effective in the coverage of buccal STD around single dental implant and the suggested prosthetic–surgical approach was aesthetically successful.